ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Yulianto, Widyasasi (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The objective of this research is to obtain empirical evidence about the effect of capital structure, firm growth, dividend policy, profitability and investment decision to firm value on manufacturing companies listed in the Indonesia Stock Exchange for the year 2015-2017. This study used a sample of 72 manufacturing companies selected using purposive sampling method. The data used are secondary data in the form of financial statements. The statistical method used to test the research hypothesis is the multiple linear regression method in which the test is performed on panel data. The results of this research are firm age and profitability have positive effect on firm value. Meanwhile financial leverage and dividend policy has no effect on firm value.